The importance of neutral hydrogen for the maintenance of the midlatitude winter nighttime ionosphere: Evidence from IS observations at Kharkiv, Ukraine, and field line interhemispheric plasma model simulations. Issue 7 (19th July 2016) - Kotov, D. V.; Richards, P. G.; Bogomaz, O. V.; Chernogor, L. F.; Truhlik, V.; Emelyanov, L. Ya.; Chepurnyy, Ya. M.; Domnin, I. F.
Abstract: This study investigates the causes of nighttime enhancements in ionospheric density that are observed in winter by the incoherent scatter radar at Kharkiv, Ukraine. Calculations with a comprehensive physical model reveal that large downward ion fluxes from the plasmasphere are the main cause of the enhancements. These large fluxes are enabled by large upward H + fluxes into the plasmasphere from the conjugate summer hemisphere during the daytime. The nighttime downward H + flux at Kharkiv is sensitive to the thermosphere model H density, which had to be increased by factors of 2 to 3 to obtain model‐data agreement for the topside H + density. Other studies support the need for increasing the thermosphere model H density for all seasons at solar minimum. It was found that neutral winds are less effective than plasmaspheric fluxes for maintaining the nighttime ionosphere. This is partly because increased equatorward winds simultaneously oppose the downward H + flux. The model calculations also reveal the need for a modest additional heat flow from the plasmasphere in the afternoon. This source could be the quiet time ring current. Key Points: Hydrogen density is important in the development of nighttime Nm F 2 enhancements at midlatitudes NRLMSISE‐00 model H density should be increased by factors of 2 to 3 at solar minimum The increase of hm F 2 has a small effect on the nighttime Nm F 2